6 Vaccine injury redress programmes: a systematic integrative review. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Keane, Martin; Moloney, Tonya; Lee, Caitriona; O'Sullivan, Michael; Long, Jean
Abstract : Objectives: This review investigated the design features of vaccine injury redress programmes that are thought to impact on the operating costs, timely access to compensation, number of applicants, and the volume and costs of awards. In addition, we ascertained if such programmes enjoy public acceptance. Vaccine injury redress programmes are available in 20 jurisdictions; only 11 jurisdictions have completed detailed papers on their set up and operation, namely, China, Denmark, Finland, Japan, Korea, Norway, New Zealand, Sweden, Taiwan, UK, and USA. Method: We chose the Integrative Review approach to synthesise an array of theoretical and empirical data to answer our questions. We searched in MEDLINE, CINAHL, Scopus, Web of Science, Cochrane Library, HeinOnline and LegalTrac. We identified 2, 838 papers and selected 33 papers that provided relevant data to answer at least one of our questions. We developed a conceptual schema based on key design features of vaccine injury redress programmes to code and extract data. The design features identified were: approach, administrator, funding source, vaccines covered, injuries covered, claims and decisionmaking process, standard of proof, litigation rights, costs awarded, and cost controls. We analysed the data using the constant comparative method as none of the papers included in our review asked either the same or similar questions to ours. Results: The treatment injury compensation scheme in New Zealand and the drug injury scheme in the four Nordic countries have improved access to compensation by removing the concept of negligence and lowering the standard of proof required. Removing negligence has also reduced administrative and legal costs in the five countries. Public awareness of and support for the scheme is high in New Zealand and it has buy-in from physicians. The schemes in these five countries are aligned to national employment insurance schemes and publicly funded health care. The USA, UK and four countries in Asia operate standalone vaccine injury redress programmes. The USA, UK and China employs a strict standard of proof which reduces timely access to redress and keeps the approval rate for claims low. Korea and Taiwan operate a more relaxed standard of proof, and Taiwan resolves claims in a timely fashion. In Japan, higher compensation is awarded to claimants judged to have protected 'the herd immunity'. Conclusions: Vaccine injury compensation is implemented to protect the supply of vaccines and improve vaccine confidence to encourage high vaccination rates among the general population. A secondary objective is to provide timely access to compensation in the event of injury from a vaccine. Schemes that have removed the need to prove negligence and apply a low standard of proof provide timely access to compensation; these schemes also reduce administrative, legal and overhead costs and improves relations between claimants and the medical profession. Schemes that apply a higher standard of proof and enact a cumbersome claim handling and adjudication process delay timely access to compensation and reduce the number of awards. Schemes vary in the level of public awareness and support that they enjoy.